Akibat Hukum terhadap Investor karena Adanya Penghapusan Pencatatan (Forced Delisting) Perusahaan Terbuka di Pasar Modal - Ida Bagus Rama Pratistha; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Jurnal Konstruksi Hukum, 2022)
The advancement of the technology era has made the Capital Market the most popular investment instrument today. The capital market is a high risk investment instrument due to the forced delisting of shares in the Capital Market. The purposes of this study are to reveal the regulation of forced delisting in the capital market and the legal consequences for investors due to forced delisting of public companies in the capital market. This research is a normative legal research with a statutory and conceptual approach. The sources of legal materials used are primary and secondary sources of legal materials which are collected using an inventory technique and then analyzed normatively in order to interpret the law (interpretation). Based on the results of the study, it is known that the regulation regarding delisting has been stated in the Capital Market Law and the Indonesian Stock Exchange regulations but there is no form of regulation that protects investors if the company experiences Forced Delisting. The legal consequences that are felt are the contamination of the company's reputation and the company's shares will lose interest, and for investors, investors will lose their investment.